THE ANALYSIS OF CHANGES OF NORMATIVE LEGAL ACTS AFFECTING THE IMPLEMENTATION OF PROCUREMENT OF SMALL AND MEDIUM-SIZED BUSINESS - T. Lysenko (Вестник университета)
The article notes the lack of growth in the share of small business in the Russian economy over the past 15 years, and indicates the need to change the current situation. This article focuses on the way to stimulate the development of small and medium-sized businesses (hereinafter referred to SMBs), namely to provide the support measures for public procurements and purchases on the Federal Law № 223-FZ. The last changes in normative legal acts affecting implementation of purchases on the Federal Law № 223-FZ, a special place in which is given to the support of small and medium business, are considered. The need for additional support measures is justified.